Third Order Nonlinear Optical , Electrochemical, Catalytic and Antibacterial Properties of Green Synthesized BaSnO3 Nanoparticles - Murugesan Suganya; Chembian Kayathiri; Rajavelu Balu; Gandhiraj Vinitha; Zion Delci; Saravanan Chitra Devi; Kaliyamoorthy Devendran; Mathiyalagan SriramRaj (Iranian Journal of Materials Science and Engineering)
Perovskite materials are widely studied for their super-conducting, magnetic, catalytic and electro-optic properties. Among them, barium stannate (BaSnO3), finds applications in dielectric and optically active devices, thermally stable capacitors, humidity and gas sensors. In this study, BaSnO3 was synthesized by chemical and greener methods and comparative analyses has been performed on their electrochemical, third order nonlinear, dye deactivation and bacterial suppression properties. Decreased crystallite size was realized for the green synthesized BaSnO3. Energy band gaps were 3.23 and 3.04 eV for BaSnO3 synthesized by normal and greener approach, respectively. The extract mediated sample exhibited increased specific capacitance value. Photocatalytic degradation efficiencies were 78.4% and 89.7%, respectively for BaSnO3 synthesized by normal and greener approach against methyl violet after 90 min of UV light irradiation. Enhanced nonlinear optical parameters were obtained for the extract mediated BaSnO3. Excellent antibacterial efficacy against Proteus vulgaris bacteria was realized for the greener BaSnO3 NPs thanks to the domination of phytochemicals of M. olifera leaf extract.